Beta-adrenergic receptor blocking therapy for congestive heart failure: an overview - mohan, JC (Nepalese Heart Journal, 2000)
It is uncommon for clinical trials to be prematurely terminated because of formidable evidence in favour ofa particular agent or strategy and rare for such trials to be reported in lay press. This is what has precisely happened with regard to beta-adrenoceptor blocking therapy in patients with congestive heart failure twice once in 1996 and again in March, 2000. The drug in question has been carvedilol (a beta-adrenergic receptor blocking agent) and the trials were Carvedilol US Heart Failure Study and GOPERNICUS (Carvedilol Prospective Randomised Cumulative Outcome Study). The therapy in patients of congestive heart failure has shown a remarkable change over a period of last three decades ever since it was shown by a Swedish team that in some patients with heart failure, beta-blocking agents can cause symptomatic improvement in refractory heart failure. The current theme is no longer symptomatic relief which is variable butsurvival benefits and less need for cardiac transplantation and recurrent hospitalization.Saga of beta-blocker therapy taught us how mechanistic approach and experimental data do not always provide the correct answer to a complex pathophysiological syndrome.